2014
DOI: 10.1007/978-3-319-07566-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Shortest Unique Substring Query Revisited

Abstract: Abstract. We revisit the problem of finding shortest unique substring (SUS) proposed recently by [6]. We propose an optimal O(n) time and space algorithm that can find an SUS for every location of a string of size n. Our algorithm significantly improves the O(n 2 ) time complexity needed by [6]. We also support finding all the SUSes covering every location, whereas the solution in [6] can find only one SUS for every location. Further, our solution is simpler and easier to implement and can also be more space e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 5 publications
(11 reference statements)
0
28
0
Order By: Relevance
“…In addition to the related work discussed in Section I, there were recently a sequence of work on finding shortest unique substrings (SUS) [15], [16], [17], [18], [1], of which Hu et al [1] studied the generalized version of SUS finding: Given a string position interval [x..y], 1 ≤ x ≤ y ≤ n, find SUS y x , the shortest unique substring that covers the string position interval [x..y], or the fact that such SUS y x does not exist. To the best of our knowledge, no efficient reduction from LR finding to SUS finding is known as of now.…”
Section: Prior Work and Our Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the related work discussed in Section I, there were recently a sequence of work on finding shortest unique substrings (SUS) [15], [16], [17], [18], [1], of which Hu et al [1] studied the generalized version of SUS finding: Given a string position interval [x..y], 1 ≤ x ≤ y ≤ n, find SUS y x , the shortest unique substring that covers the string position interval [x..y], or the fact that such SUS y x does not exist. To the best of our knowledge, no efficient reduction from LR finding to SUS finding is known as of now.…”
Section: Prior Work and Our Contributionmentioning
confidence: 99%
“…Given the lcp and rank arrays of the string S, we can compute its useful LLRs in O(n) time and space. Proof: By Lemma 2, we know if LLR i−1 exists, the right boundary of LLR i is on or after the right boundary of LLR i−1 , for any i ≥ 2, so we can construct the array of useful LLRs in one pass as follows: we calculate each LLR i using Lemma 1, , 8), (7,13), (10,14), (11,17)}, where each useful LLR is a (start, end) tuple, representing the start and ending position of the LLR. By viewing the start and end positions as the x and y coordinates, all the useful LLRs of the example string can be visualized as the dark dots in the figure. (B) Queries for LR 12 11 , LR 14 11 , LR 12 6 and LR 5 5 are visualized by the red, blue, green, and black polylines, numbered A -D , respectively.…”
Section: A Geometric Perspective Of the Useful Llrs And The Lr Qumentioning
confidence: 99%
See 1 more Smart Citation
“…It thus remains to give a structure for finding Candidate 4. [3,6], [6,7], [7,10] We want to store I in a data structure to answer such queries efficiently.…”
Section: A 4-candidate Lemmamentioning
confidence: 99%
“…In their initial study [9], Pei et al showed how to construct in O(n 2 ) time an index of O(n) size that answers a query in O(1) time. Soon after that, Ileri et al [6] and Tsuruta et al [10] independently improved the construction time to O(n). It is worth mentioning that O(n) size is considered optimal in the sense that D itself requires Ω(n) words to store when the alphabet is large.…”
Section: Introductionmentioning
confidence: 99%